Analisis Manajemen Dalam Pengembangan Kompetensi Pendidik Madrasah Tsanawiyah - Nur Fauzi; Giyoto Giyoto; Fauzi Muharrom (Jurnal Ilmiah Ekonomi Islam, 2021)
Management in madrasah education, in addition to the role of the principal, is also the role of supervisors or supervisors who are also a determinant in improving learning achievement and school quality. Education supervision or supervision is an effort to provide services to education stakeholders, especially to educators at school, both individually and in groups to improve the quality of the learning process and results, the purpose of this study is to conduct management analysis for the development of educational competence in madrasah tsanawiyah in Demak district. This research method, carried out through a qualitative approach using descriptive method of case study strategies. This study describes or describes the phenomenon of teacher competency development in classroom management. The results showed that in Madrasah Tsanawiyah, Demak Regency, showed that policies made both from planning, implementation, support and obstacles, and the impact of developing teacher professional competence which were carried out were carried out according to goals and planned although there were still obstacles and shortcomings that still had to be addressed.